Key Management Ratios: The clearest guide to the critical numbers that drive your business (4th Edition) (Financial Times Series) - Walsh (Management, 2012)
Business ratios are the figures that provide management with targets and standards for their organisation. They direct businesses towards the most beneficial long-term strategies, as well as towards effective decision making.